Baicalein Restores the Balance of Th17/Treg Cells via Aryl Hydrocarbon Receptor to Attenuate Colitis - Chang Liu; Yanyang Li; Yanping Chen; Shaowei Huang; Xiaojing Wang; Shuang Luo; Yulin Su; Lian Zhou; Xia Luo (Mediators of Inflammation)
As one of the ligands of aryl hydrocarbon receptor (AhR), baicalein, isolated from Scutellaria baicalensis Georgi, has been proved to exert potential therapeutic effects on ulcerative colitis (UC), but its therapeutic mechanism remains obscure. Authentically, ulcerative colitis can be alleviated by regulating the differentiation of naïve CD4+ T cells via AhR activation. So, our study planned to prove the hypothesis that baicalein protected mice against UC by regulating the balance of Th17/Treg cells via AhR activation. Immunofluorescence and western blot results showed that baicalein could promote AhR activation and induce it to transfer to the nucleus. We further determined the effect of baicalein on naïve CD4+ T cell differentiation in vitro by magnetic cell separation and drug intervention. The results showed that baicalein could promote Treg cell differentiation by activating AhR. In vivo study, UC mice were established by free drinking of dextran sulfate sodium (DSS) for 7 days and then were orally administrated by baicalein (10, 20, and 40 mg/kg), TCDD (AhR agonist), and CH223191 (antagonist). The results demonstrated that baicalein improved the symptoms of UC mice, regulated the balance of Th17/Treg cells, and restored the balance of proinflammatory cytokines such as IL-17, IL-6, and TNF-α; anti-inflammatory cytokines such as IL-10 and TGF-β; and epithelial protective cytokine IL-22 in UC mice, and these effects were related to AhR. Taken together, our research found that baicalein might be a potential drug for UC via regulating Treg cell differentiation and maintaining immune homeostasis and attempted to shed a light on the pivotal role of AhR in these effects.